2021
DOI: 10.3389/fphys.2021.626707
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Function of Sympathetic Innervation on the Endo/Lysosomal Trafficking of Acetylcholine Receptor

Abstract: Recent studies have demonstrated that neuromuscular junctions are co-innervated by sympathetic neurons. This co-innervation has been shown to be crucial for neuromuscular junction morphology and functional maintenance. To improve our understanding of how sympathetic innervation affects nerve–muscle synapse homeostasis, we here used in vivo imaging, proteomic, biochemical, and microscopic approaches to compare normal and sympathectomized mouse hindlimb muscles. Live confocal microscopy revealed reduced fiber di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 118 publications
(174 reference statements)
0
19
0
Order By: Relevance
“…31 Although the role of the autonomic nervous system, particularly noradrenergic neurons, in higher brain function in health and disease has been studied for some time, [32][33][34][35] research on its involvement in controlling neuromuscular transmission, skeletal muscle innervation and mass, and motility, is more recent. [22][23][24][25][26][27][28] Three noradrenergic neuron clusters-A5, A6, and A7show extensive descending projections to the spinal cord. The A5 group projects segmentally to A6, with a possible role in cognition, and spinally, to target pre-ganglionic cholinergic neurons in the intermediolateral column (IML).…”
Section: Noradrenergic Neurons Exhibit Complex Interconnections and P...mentioning
confidence: 99%
See 2 more Smart Citations
“…31 Although the role of the autonomic nervous system, particularly noradrenergic neurons, in higher brain function in health and disease has been studied for some time, [32][33][34][35] research on its involvement in controlling neuromuscular transmission, skeletal muscle innervation and mass, and motility, is more recent. [22][23][24][25][26][27][28] Three noradrenergic neuron clusters-A5, A6, and A7show extensive descending projections to the spinal cord. The A5 group projects segmentally to A6, with a possible role in cognition, and spinally, to target pre-ganglionic cholinergic neurons in the intermediolateral column (IML).…”
Section: Noradrenergic Neurons Exhibit Complex Interconnections and P...mentioning
confidence: 99%
“…Cholinergic neurons (Ch1–Ch6) are found in the pons and midbrain and non‐brainstem areas, such as the thalamus and pre‐ganglionic neurons located in the spinal cord intermediolateral column 1,19 . They regulate wake/sleep cycles 20,21 and, together with noradrenergic neurons, provide the final peripheral sympathetic pathway for regulation of neuromuscular transmission and skeletal muscle innervation 22–28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While SNs were identified several years ago, in anatomic studies, to account for a significant fraction of the neuronal types in nerves directed to hindlimb muscles ( Straka et al, 2018 ; Di Bona et al, 2020 ), their initial role was restricted to the regulation of muscle blood vessel diameter, which is coherent with the adaptative response to physical exercise ( Lombard and Cowley, 2012 ). Nonetheless, several recent reports, using refined imaging methods and pharmacologic approaches, have shown that SNs interact with muscle fibers and play initially unsuspected functions, ranging from the modulation of synaptic transmission between MNs and muscle cells, to the maintenance of morphological and functional stability of the NMJ ( Khan et al, 2016 ; Straka et al, 2018 , 2021 ). In addition, noradrenaline stimulation of muscle fibers leads to increase in contraction force, via PKA activation, and subsequent phosphorylation of downstream targets, involved in the mechanism of cell shortening (i.e., L-type Ca 2+ channels; ryanodine receptors; Cairns and Dulhunty, 1993 ; Röder et al, 2009 ; Rudolf et al, 2013 ; Khan et al, 2016 ; Straka et al, 2021 ).…”
Section: Multiple Roles Of Neuro-muscular Innervationmentioning
confidence: 99%
“…Nonetheless, several recent reports, using refined imaging methods and pharmacologic approaches, have shown that SNs interact with muscle fibers and play initially unsuspected functions, ranging from the modulation of synaptic transmission between MNs and muscle cells, to the maintenance of morphological and functional stability of the NMJ ( Khan et al, 2016 ; Straka et al, 2018 , 2021 ). In addition, noradrenaline stimulation of muscle fibers leads to increase in contraction force, via PKA activation, and subsequent phosphorylation of downstream targets, involved in the mechanism of cell shortening (i.e., L-type Ca 2+ channels; ryanodine receptors; Cairns and Dulhunty, 1993 ; Röder et al, 2009 ; Rudolf et al, 2013 ; Khan et al, 2016 ; Straka et al, 2021 ). Furthermore, noradrenaline release by muscle-innervating SNs regulates myocyte trophism, through activation of β2-adrenoceptors (β2-ARs), which modulate protein degradation, by negatively impinging on the expression of atrophic gene patterns ( Navegantes et al, 2004 ; Rudolf et al, 2013 ).…”
Section: Multiple Roles Of Neuro-muscular Innervationmentioning
confidence: 99%